Performance analysis of Fuzzy VM Management techniques for Task scheduling on Cloud systems - Kulkarni, RA; Patil, SB; Balaji, N (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing has been widely adopted by many industries as a platform to support distributed applications. Cloud provides the advantages of reduced operation costs, flexible system configuration and elastic resource provisioning. Even though cloud has been rapidly getting adopted there are various open challenges in areas such as management of virtual resources, security and organizational issues. One of the prominent technologies used by cloud computing is the virtualization. The virtualization technology faces tremendous challenges in supporting real-time applications on cloud as these applications demand real-time performance in open, shared and virtualized computing environments. In this paper we are analyzing the usage of fuzzy logic in improving the performance of time constrained tasks. Our proposed system makes use of fuzzy logic in scheduling of tasks to Virtual machines and in identification of destination host in migrating the overloaded virtual machines which can give better performance than the traditional scheduling algorithms used on cloud systems.